SEX DETERMINATION FROM FINGERPRINTS AMONG SOUTH INDIAN POPULATION (Journal of Forensic Medicine & Toxicology, 2021)
Person identification has always been an important aspect in every phase of investigation. The stature, sex, age and race are the basic features that we look for. Fingerprints were always a reliable source for individual identification. It is unique, universal, non-replicable form of evidence which differ from person to person and even within finger
Keywords: fingerprints; DNA; Two hundred